Organic Modification of Chitosan: An Overview - Mohammed Al-Mashhadani; Hadeel Adil; Huda Ghazi Naser; Hanan A. Ibraheem; Rasha Saad Jwad; Sohad A. Alshareef; Amer Adnan Hasan; Sanjay Ghosh; Hussein A. Hamzah; Emad Yousif (Baghdad Journal of Biochemistry and Applied Biological Sciences)
Alkaline deacetylation of chitin yields chitosan, a naturally occurring polymer with remarkable biological qualities like immunological, antibacterial, and wound healing capabilities. Recently, there has been an increase in interest in modifying chitosan chemically to increase its solubility and expand its uses. The usual method for obtaining chitosan is to deacetylate chitin in an alkaline environment. Chitin is one of the most common organic molecules, generated by biosynthesis, second only to cellulose yearly. Chitin plays a significant role in the exoskeleton of animals, particularly insects, mollusks, and crustaceans. It is also the main fibrillar polymer found in some fungi’s cell walls. Composed of glucosamine and N-acetyl glucosamine units connected by β (1–4) glycosidic linkages, chitosan is a linear polysaccharide. The degree of deacetylation refers to the amount of glucosamine present. Actually, in a broad sense. This study reviews the major chitosan chemical changes that have been suggested in the literature. Furthermore, a wide variety of derivatives with a wide range of uses are produced by these chemical alterations. Instances of recent and pertinent instances of the various uses are provided with a focus on tissue engineering, medication delivery, and environmental applications. Looking ahead, the future of chitosan modification appears bright, driven by advancements in smart polymers, green chemistry, and nanotechnology. These developments are facilitating the creation of tailored materials with diverse applications, further expanding the potential utility of chitosan in various fields.